KOMPONEN HASIL DAN PRODUKSI KACANG TANAH (Arachis hipogea L.) PADA BERBAGAI KONSENTRASI TIBA DAN DOSIS PUPUK FOSFOR - Yonanda Wardemarti; Aslim Rasyad; Nurbaiti Nurbaiti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The objectives ofthis study is to determine the effect of TIBA concentration under different phosphorus fertilizer on yield and yield component of peanut (Arachis hypogea L.). A field experimentwas conducted in the Faculty of Agriculture experimental station, University of Riau from Agustus to November 2015 and arranged in a split  plot design with three replications.Three levels of TIBA concentration; ie, 0, 50 ppm, and 75 ppm were assigned as main plot and four levels of phosphorus fertilizer; ie,0, 11,5, 23, and 34,5 kgperhaP2O5were assigned as subplot. Seed of Jerapah variety was sown in a plot of 2,25 m length and 2 m wide with planting space of 40 cm x 15 cm. Yield components and yield were recorded from each plot and then analyzed by using SAS Program. The result showed that application of 75 ppm TIBA produced significantly greater number of filled pods per plant, seed weight per plant, pod dry weight and seed yield per m2 than of 50 ppm TIBA and control. In the other hand, application of 34,5 kg/ha P2O5produced more filled number per plant, seed weight per plant, pod dry weight and seed yield per m2 than other P fertilizer rates. So that, it is advisable to grow peanut plant  by applying 34,5 kgP2O5 per ha and application of 75 ppm TIBA at 28 days after planting. Keywords:peanut, TIBA concentration,  phosphorus fertilizer yield component